PERANGKAP KUANTIFIKASI DALAM SUSTAINABILITY BALANCED SCORECARD: ILUSI PRESISI DALAM PENGUKURAN ISU SOSIAL DAN ETIKA DI SEKTOR PERTAMBANGAN - Levina Aprilia Valda; Kurnia Ekasari; Hesti Wahyuni (Jurnal Ilmiah Akuntansi, 2026)
This conceptual article examines the “quantification trap” in the Sustainability Balanced Scorecard (SBSC), which is the tendency to treat numbers as clear and certain proof of social and ethical performance, even though they often reflect only inputs or administrative outputs. Using a critical literature review for the 2020-2025 period and the Theory of Change (ToC) lens, the article applies a reconstruction approach by mapping indicators from the 2024 Sustainability Reports of PT Adaro Andalan Indonesia Tbk and PT Vale Indonesia Tbk into the four Balanced Scorecard perspectives as a framework to reconstruct an SBSC (Learning and Growth, Internal Process, Stakeholder, and Financial). The review finds that many indicators are easy to count, such as training hours, the Community Satisfaction Index, Social Return on Investment, the percentage of complaints resolved, and “zero cases” integrity numbers. These indicators can create an illusion of precision and lead to wrong classification of social and ethical performance when they are not linked to outcomes and real impacts. The findings also show a contrast in measurement quality: safety metrics are usually stronger because they use clear ratios with clear denominators, while social and ethics metrics often stop at aggregated numbers or process outputs. This article proposes redesigning SBSC indicators using ToC through input-output-outcome ratios and leading-lagging pairing to improve measurement quality, clarify cause-and-effect links, and strengthen managerial recommendations for the Indonesian mining sector.